2020
DOI: 10.2478/eces-2020-0020
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics Resistance inEnterococcusIsolates From Poultry Waste

Abstract: The aim of the study was to evaluate the drug resistance of Enterococcus faecalis and Enterococcus faecium isolated from different types of poultry waste. The study material consisted of feather samples (duck, turkey, chicken), sludge and centrifuge sediment, originating from three poultry farms. The study was conducted in two stages; isolation and identification of Enterococcus bacteria from the waste and evaluation of their drug resistance using Kirby-Bauer method. Contamination of the poultry waste with Ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The role of fsr complexes in biofilm formation was also reported previously (Cybulska et al, 2020). In an Indian survey (Biswas et al, 2019), isolates of the present survey.…”
Section: Surveys Conducted Bysupporting
confidence: 83%
See 2 more Smart Citations
“…The role of fsr complexes in biofilm formation was also reported previously (Cybulska et al, 2020). In an Indian survey (Biswas et al, 2019), isolates of the present survey.…”
Section: Surveys Conducted Bysupporting
confidence: 83%
“…As some isolates harbored a high resistance towards human‐based antimicrobial agents (those are basically used to treat human infectious diseases), it can be indirectly concluded that these isolates originated from infected staffs of seafood sales and processing centres (Ranjbar et al., 2019). The high resistance rate of E. faecalis strains isolated from food samples towards oxacillin, tetracycline, erythromycin, cefoxitin, cefazolin, trimethoprim‐sulfamethoxazole, rifampin, clindamycin, and gentamicin antimicrobial agents was reported from Switzerland (Boss et al., 2016), Turkey (Sanlibaba et al., 2018), Slovakia (Kročko et al., 2011), Africa (Olawale et al., 2015), Poland (Cybulska & Krzyśko‐ŁUpicka, 2020), and South Korea (Kim et al., 2021). Sergelidis et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The turkey samples were the source of 30 C. jejuni strains and 1 C. coli strain, while the number of C. jejuni and C. coli isolates from the broiler faeces was 11 and 3, respectively minimum inhibitory concentration (MIC); molecular methods Strains susceptible to azithromycin, erythromycin, gentamicin, florfenicol, telithromycin, clindamycin; all strains resistant to ciprofloxacin; 92.9% strains from broiler resistant to nalidixic acid and 78.6% strains resistant to tetracycline; 83.9% strains from turkey resistant to nalidixic acid and 58.1% % strains resistant to tetracycline all strains resistant to ciprofloxacin had a mutation in the gyr A gene at Thr-86 position; presence of the tet O gene in 71% of isolates from the turkey and in100% of isolates from the broiler; all strains resistant to tetracyclines contained the tet O gene; 5 strains from turkey faeces and 3 strains from broiler faeces susceptible to tetracycline contained the tet O gene Woźniak-Biel et al 2018 (PL) 3 poultry farms various waste materials collected on poultry farms: 4 feather samples (duck, turkey, chicken), sludge (2 samples) centrifuge sediment (2 samoles) selective medium 100 strains of Enterococcus genus identified as Enterococcus faecalis (21%) , Enterococcus faecium (79%) Chromogenic differentiating medium ChromID VRE; disc diffusion method More than 50% of the strains demonstrated resistance to 19 out of 23 antibiotics. The highest resistance in the case of streptogramins, carbapenems, fluoroquinolones, aminoglycosides, penicillins; the lowest in the case of nitrofurantoin and chloramphenicol; E. faecalis strains were more resistant than the E. faecium; presence of multidrug resistance of isolates - Cybulska and Krzyśko-Łupicka 2020 (PL) environmental samples from chicken broilers, turkey broilers and laying hens; 51 isolates from 2 veterinary laboratories originated from livestock environment; n/a Salmonella enterica ser. Enteritidis minimum inhibitory concentration (MIC); molecular methods all isolates susceptible to gentamicin, tazobactam, cefotaxime, meropenem, azithromycin, tigecycline and trimethoprim, ampicillin, 84.3% isolates resistant to colistin, 56.9% to sulfamethoxazole; 41.2% to nalidixic acid, 21.6% to tetracycline, 3.9% to chloramphenicol, 2.0% to ciprofloxacin 14 isolates showing multidrug resistance; resistance genes: flo R (51.0%), bla TEM (35.3%), bla PSE (5...…”
Section: Resultsmentioning
confidence: 99%
“…There are not many pieces of research on risk communication as a system to verify the structural relationship of variables within the system. However, there are not many similar types of research on verifying the structural relationship of conceptual dimensions [25][26][27]. In the research of sports competition anger, firstly, four dimensions of the concept of middle school students' sports competition anger are put forward, namely, anger stressor, anger cognitive evaluation, anger reaction, and anger expression, and then the mechanism of the four dimensions is discussed (Fig.…”
Section: Methodsmentioning
confidence: 99%